Internet Financial Reporting: A Bibliometric Review - Rahmawati Rahmawati; Farah Ordina Ardha Sukma; Ari Kuncara Widagdo; Endang Dwi Amperawati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: This study aims to identify the main and emerging areas of research in publications on internet financial reporting and to suggest directions for future research. Internet-based corporate reporting disclosure reflects the development of corporate information disclosure from supplementary or voluntary disclosure. Method: The method used in this study is bibliometric analysis, with a sample of 983 studies from the Scopus database on internet financial reporting between 2013 and 2024. In co-occurrence analysis, keywords are divided into 5 clusters. Results: According to this study, research publications on internet financial reporting have undergone considerable changes. More complex developments, aligned with global economic trends, are influenced by related variables. The results of the analysis indicate that some variables can be used in further research and point the way for future research in this area. Novelty: Research is expected to provide a clearer, more precise direction for future internet financial reporting research. Not only can research be conducted with variables that have been widely explored, as in repeat research, but it can also explore other variables that are more appropriate to the current situation and conditions, thereby further enriching the scientific repertoire related to internet financial reporting.